PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (STUDI KASUS BUTIK SHIFA OLSHOP MEDAN) - Zahratunnisa Zahratunnisa; Muhammad Rahmat (Jurnal Manajemen dan Bisnis, 2022)
The aim of this study is to investigate the relationship between service quality and product quality for customer satisfaction when shopping at Sippa All Shop Medan boutique. In this study, 69 individuals were selected and determined using a simple random sample. Data Collection Techniques - Distribution of interviews and questionnaires to respondents who shop frequently at shifa olshop boutiques. The data analysis methods used are descriptive analysis and multiple linear regression analysis. The analysis showed that service quality (X1) and product quality (X2) had a positive and significant effect on customer satisfaction (Y) of Shifa Olshop Boutique Medan. In the test, the coefficient of determination (R2) is used to determine the ability of the independent variable used in the regression equation to account for the dependent variation. This value obtained from the modified Rsquared has a value of 0.706, which means that the relationship between the two independent variables of the dependent variable changes by 70.6%, or it can be said that customer satisfaction can be explained by service quality and product quality. The remaining 29.4% was due to other factors not considered in this study.